ANALISIS PREDIKSI KEBANGKRUTAN DENGAN MENGGUNAKAN METODE Z SCOREALTMAN PADA PERUSAHAAN TELEKOMUNIKASI YANG GO PUBLIC - Indramasrin -; Nurhidayah M (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2018)
PT. Telekomunikasi is a company that has many competitors in business and competes in order to get profit. A company that cannot adapt itself in this situation, it will experience bankruptcy. The aim of this journal is to know the prediction of bankruptcy of PT Telekomunikasi registered in Indonesia Stock Exchange in period of 2014-2016 using Z-Score Altman method. Data analysis technique used in this journal is Z-Score bankruptcy analysis from Altman. The result of this research, from three companies registered in Indonesia Stock Exchange that go public, there is only a company that will prone to bankrupt that is PT. Telekomunikasi Indonesia Tbk. The other two companies in state of bankruptcy are PT. Indosat and PT. XL Axiata. All three companies have the same z value that is z <1,81. The company that is prone to bankrupt should increase sales and reduce debt with the principle of cost efficiency. The company in state of bankruptcy should improve its financial condition.Keyword : Bankruptcy, Indonesia Stock Exchange, Z